Digital inclusion across the Americas and the caribbean - Robinson, L.; Schulz, J.; Dodel, M.; Correa, T.; Villanueva-Mansilla, E.; Leal, S.; Magallanes-Blanco, C.; Rodriguez Medina, L.; Dunn, H.S.; Levine, L.; McMahon, R.; Khilnani, A. (Cogitatio Press, 2020)
This research brings together digital inequality scholars from across the Americas and Caribbean to examine efforts to tackle digital inequality in Uruguay, Chile, Peru, Brazil, Mexico, Cuba, Jamaica, the United States, and Canada. As the case studies show, governmental policy has an important role to play in reducing digital disparities, particularly for potential users in rural or remote areas, as well as populations with great economic disparities. We find that public policy can effectively reduce access gaps when it combines the trifecta of network, device, and skill provision, especially through educational institutions. We also note, that urban populations have benefitted from digital inclusion strategies to a greater degree. This underscores that, no matter the national context, rural-urban digital inequality (and often associated economic inequality) is resistant to change. Even when access is provided, potential users may not find it affordable, lack skills, and/or see no benefit in adoption. We see the greatest potential for future digital inclusion in two related approaches: 1) initiatives that connect with hard-to-reach, remote, and rural communities outside urban cores and 2) initiatives that learn from communities about how best to provide digital resources while respecting their diversely situated contexts, while meeting social, economic and political needs.
Keywords: Digital inequality; Public policy; Rural-urban divide; https://purl.org/pe-repo/ocde/ford#5.04.04